(untitled) (The Pakistan Development Review, 1986)
Much interest has recently been shown in the effects of regional trade co-operation among developing countries on their trading patterns. This interest stems from the potential for facilitating development in a group of developing countries through preferential arrangements and from the expectation of significant mutual trade gains. However, the experience of the implementation of discriminatory policies among the developing countries has, in general, not yielded significant gains in trade. An important exception is the Andean Pact, which provided an important stimulus to the regional movement in Latin America.